PENGARUH FASILITAS PERPAJAKAN, RETURN ON ASSET, LEVERAGE, UKURAN PERUSAHAAN, DAN INTENSITAS ASET TETAP TERHADAP MANAJEMEN PAJAK - MARIA DEVINA; ARYA PRADIPTA (E-Jurnal Akuntansi TSM, 2021)
This study aims to examine, analyze and obtain empirical evidence about the effect of the tax facility, return on assets, leverage, company size and intensity of fixed assets to tax management. The population of this research is a non-financial services company listed on the Indonesia Stock Exchange for 2013-2015. The population in this study are 230 service companies. The sampling technique used in this research is purposive sampling. This sampling obtained 53 service firms samples that are based on certain criteria that have been set. These results indicate that the tax facility, return on assets, leverage, and the size of the company does not affect to tax management while the intensity of fixed assets negatively affect to tax management.